Oral cancer in Malaysia: Awareness, etiology, prognosis, quality of life and early detection / Wan Maria Nabillah Wan Abdul Ghani - Wan Maria Nabillah, Wan Abdul Ghani (2019)
It is well established that oral cancer occurs more commonly in developing countries rather than developed countries. Prognosis of patients is poor, mostly attributed to the presentation of disease at advanced stages. The visibility of the tumor, which is located at the head and neck region, further affects the quality of life of these patients. Variations in the risk factors for oral cancer across different geographical regions have also been documented. However, data with regards to oral cancer among the Malaysian population is severely lacking. Realizing the debilitating impact of oral cancer, and in view that it is ranked within the top ten most common cancers among ethnic Indians in Malaysia, the need for information on oral cancer in Malaysia is imperative. In this thesis, a series of original published works on oral cancer in the Malaysian context are presented. These studies encompass a wide spectrum, ranging from i) before the onset of disease; assessing the level of awareness and etiological factors, ii) impact of disease; evaluating the prognosis and quality of life of patients, to iii) secondary prevention of disease; exploring potential tools for the purpose of early detection. Firstly, the awareness level of the Malaysian public on oral cancer was assessed. Awareness was found to be poor, whereby only about half of the respondents knew of the risk habits and signs and symptoms of oral cancer. Interestingly, gender and ethnic differences were observed in their level of awareness. Mass media was quoted as the main source of information on oral cancer, however our study found that information dissemination through mass media did not confer a significant improvement in the knowledge of the public on signs and symptoms associated with oral cancer. Following this, we conducted studies on the etiology of oral cancer. The role of tobacco smoking, alcohol drinking and betel quid chewing as risk factors for oral cancer and its synergistic effect were further validated in our study. Findings showed that there iv were significant differences in the practice of these risk habits across the different ethnic groups. Further analysis revealed that habit initiation was influenced by gender, ethnicity and combined practice of other risk habits, whereas cessation was associated with practice of another risk habit and the type of cigarette smoked or betel quid chewed. Findings on the etiological role of dietary intake showed that a reported diet pattern loaded with consumption of meat, dairy, fermented food, carbonated beverages and caffeine increased cancer risk, whereas a high intake of fruits and vegetables decreased the risk for oral cancer. In terms of assessing the disease impact, we determined the prognosis of Malaysian oral cancer patients. The 5-year survival rate was observed to be slightly poorer than the world average statistics. No significant ethnic difference was found in the prognosis of these patients. Larger tumor size, lymph node metastasis and advanced disease stage were elucidated as reliable indicators of prognosis. Apart from clinical factors, the potential of biomarker as an indicator of prognosis was also investigated. Our study on the collagen triple helix repeat containing-1 (CTHRC1) gene showed that high expression of CTHRC1 conferred a poorer patient survival, indicating the utility of this biomarker as a method for prediction of prognosis. In addition, the impact of oral cancer on patients’ health related quality of life (HRQoL) was assessed. At pre-treatment, HRQoL of patients with early stage disease was observed to be better than patients with advanced disease. Significant deterioration in some HRQoL domains were evident until three months post-treatment for advanced stage patients, whereas early stage patients did not show any further significant HRQOL deterioration at three months post-treatment. In Malaysia, the majority of oral cancers are detected at advanced stages. As it has been established that late stage disease influences patient’s prognosis and quality of life, the need for early detection cannot be overemphasized. Thus, we explored the v efficacy of mouth self-examination (MSE) as a possible tool for early detection of oral diseases. Most of the respondents were observed to have difficulties in performing MSE. Although specificity of MSE was high, sensitivity of MSE in detecting lesions was found to be low. Besides MSE, we also evaluated the feasibility of teledentistry as a method for early detection of diseases. Our findings indicated that sensitivity and specificity of teledentistry in detecting lesions were high. Furthermore, it was observed that teledentistry was able to differentiate between malignant and non-malignant lesions. In summary, the presentation of oral cancer at advanced stages had impacted the quality of life and prognosis of Malaysian oral cancer patients. In addition, we found that genetic changes could be a potential tool for prediction of prognosis. The general lack of awareness among the Malaysian public and the practice of multiple oral cancer risk habits suggests the need for educational intervention. As gender and ethnic differences were evident in the level of awareness and practice of these habits, interventional educational programs designed specifically to cater to the needs of each ethnic group would be most ideal. We also showed the potential of utilizing the concept of teledentistry as an alternative method for early detection of disease. However, at this point, our findings were unable to provide sufficient evidence to advocate the usage of MSE as a tool for early detection.